Human Visceral Leishmaniasis: a Serological Survey in Rural Areas of Dashti District of Bushehr Province, Southern Iran - Gorgipoor, Mohammad; Mohebali, Mehdi; Akhoundi, Behnaz; Abbaszadeh Afshar, Mohammad javad; Kazemi, Bahram; Khazaei, Sasan; Azargashsb, Eznollah; Khazan, Hooshang (Novelty in Biomedicine, 2017)
Background: Visceral leishmaniasis (VL) or kala-azar is a parasitic disease caused by the species of Leishmania donovani complex. Mediterranean type of the disease is endemic in some parts of Iran and more than 95% of cases were reported in children up to 12 years of age. This study was performed to determine the seroprevalence of VL in the rural areas of the Dashti district from Bushehr province. Materials and Methods: In this cross-sectional study, a randomized cluster sampling method was used for the collection of blood samples from children up to 12 years old from rural areas of Dashti district. Before sampling; a questionnaire was filled out for each case. All the collected blood samples were examined after the serum separating by Direct Agglutination Test (DAT) for detection of anti-Leishmania infantum antibodies. The cutoff titers of ≥1: 3200 with specific clinical features were supposed to be considered as VL. Results: Altogether, 24 out of 1221 (1.96%) blood samples showed titers between 1:800 and 1:1600 which considered as suspicious cases. None of the suspicious cases had a history of kala-azar. None of 1221 collected blood samples showed anti Leishmania infantum (L. infantum) at titer ≥1:3200. Conclusion: This study confirms the circulation of L. infantum in Dashti district and highlights the sporadic pattern of VL in the studied areas which necessitates the surveillance system to be monitored by health authorities.